2005
DOI: 10.1007/s00251-005-0041-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the interleukin-4 receptor α chain gene influence susceptibility to HIV-1 infection and its progression to AIDS

Abstract: Interleukin (IL) 4 is a key T helper-2 cytokine that downregulates and upregulates CCR5 and CXCR4, respectively, the main coreceptors for HIV. Our objective is to investigate whether single-nucleotide polymorphisms (SNPs) in the IL-4 receptor alpha chain gene (IL4RA) affect HIV infection and its progression to AIDS. The I50V SNP in exon 5 and the haplotypes of six SNPs in exon 12 (E375A, C406R, S411L, S478P, Q551R, and V554I) were studied by polymerase chain reaction and sequencing in 30 HIV+ long-term nonprog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 75 publications
0
20
0
2
Order By: Relevance
“…44 These polymorphisms are also of interest in other diseases influenced by the immune response. For I75V it is suggested that homozygosity for the V-allele associates with slow progression from HIV-1 to AIDS 45 and that the V-allele increases the risk of erosive disease in rheumatoid arthritis. 46 The Q576R polymorphism is suggested to have implications for susceptibility to HIV-1 infection 47 and multiple sclerosis 48,49 and IL-4R haplotypes have shown association with Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…44 These polymorphisms are also of interest in other diseases influenced by the immune response. For I75V it is suggested that homozygosity for the V-allele associates with slow progression from HIV-1 to AIDS 45 and that the V-allele increases the risk of erosive disease in rheumatoid arthritis. 46 The Q576R polymorphism is suggested to have implications for susceptibility to HIV-1 infection 47 and multiple sclerosis 48,49 and IL-4R haplotypes have shown association with Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is related to human papillomavirus infection and Th1 immune responses are essential for viral clearance. The IL4R I75V polymorphism was also related to other viral diseases like acquired immunodeficiency syndrome or Rous sarcoma virus bronchiolitis and thus may alter the Th1/Th2 balance [27,28]. An altered host-tumor interaction by an imbalance of Th1/Th2 cytokine expression or an altered response to these cytokines may lead to harmful processes in DLBCL patients and thereby affect the clinical course in the way shown here for the IL4R I75V gene variation.…”
Section: Discussionmentioning
confidence: 68%
“…The IL4-R alpha I50V polymorphism in exon 5 of IL-4R gene affects the functional responsiveness of the gene (Risma et al, 2002). The SNP I50V was found to be associated with slow progression to AIDS in HIV-1 infected individuals (Soriano et al, 2005). However, another study suggested an association of IL-4R alpha I50V allele with increased likelihood of HIV-1 infection in North Indian population ).…”
Section: Interleukin-4 (Il-4) and Il-4 Receptor (Il-4r)mentioning
confidence: 98%